A Restless Leg Syndrome Incidentally Detected by an 18F-FDG Positron Emission Tomography. (May 2017) - Ohnona, Jessica; Metlaine, Arnaud; Leger, Damien; Talbot, Jean-Noël
Abstract : Abstract: A case of a restless leg syndrome (RLS) was incidentally detected in a 49-year-old woman referred for an 18 F-FDG PET/CT in monitoring her breast cancer. She was treated with chemotherapy and on long-term hormone therapy. Diffuse 18 F-FDG uptake of calf muscles was visualized. Medical history revealed that the patient felt leg cramps in supine position, suggesting RLS. The diagnosis was confirmed using clinical rating scales and polysomnography. RLS being underdiagnosed, this type of FDG PET/CT incidental finding should prompt to check the presence of evocative symptoms and refer the patient to a physician specialized in sleep disorders.